Notes on marine algae in the International Biosphere Reserve Seaflower, Caribbean Colombia, VII: Additions to the benthic flora of San Andrés Island (2018)
Ten species of red macroalgae are newly reported for the Seaflower International Biosphere Reserve in the Caribbean Sea. Of these taxa, four have been previously reported for the Colombian Caribbean: Dohrniella antillarum, Halydictyon mirabile, Taenioma nanum, and Aglaothamnion cordatum. The remaining six species are new records for the country: Callithamniella tingitana, Frikkiella searlesii, Lejolisia exposita, Melanothamnus gorgoniae, Monosporus indicus, and Wrangelia gordoniae. The algal material was collected in coral reef habitats (9–17 m depth), and all species but one are diminutive algae growing mostly on coral rubble or as epiphytes on larger algae. Their morphological features are discussed.